2015
DOI: 10.1016/j.proeng.2015.01.369
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Optimization of Sintered Carbides Turning with PCD Tools

Abstract: The paper presents the results of the cutting forces research (F f , F p , F c ) when machining of sintered carbides WC-Co (25 % Co) with tools made of polycrystalline diamond PCD. Inserts with three different nose radii r ε were used during the study. Each cutting test was carried out on the distance 54 mm at the constant depth of cut 0.2 mm. The biggest increase of passive cutting force component F p was indicated. In addition, the mathematical models for cutting force value prediction as the cutting path in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Tables [6][7][8] show the ANOVA regression analysis results of the components for the Sv, Sz, and Sa parameters (where: DF-degrees of freedom, Seq SS-sums of squares, Adj SS-adjusted sums of squares, and Adj MS-adjusted means squares). Tables [6][7][8] show the ANOVA regression analysis results of the components for the Sv, Sz, and Sa parameters (where: DF-degrees of freedom, Seq SS-sums of squares, Adj SS-adjusted sums of squares, and Adj MS-adjusted means squares). Tables [6][7][8] show the ANOVA regression analysis results of the components for the Sv, Sz, and Sa parameters (where: DF-degrees of freedom, Seq SS-sums of squares, Adj SS-adjusted sums of squares, and Adj MS-adjusted means squares).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tables [6][7][8] show the ANOVA regression analysis results of the components for the Sv, Sz, and Sa parameters (where: DF-degrees of freedom, Seq SS-sums of squares, Adj SS-adjusted sums of squares, and Adj MS-adjusted means squares). Tables [6][7][8] show the ANOVA regression analysis results of the components for the Sv, Sz, and Sa parameters (where: DF-degrees of freedom, Seq SS-sums of squares, Adj SS-adjusted sums of squares, and Adj MS-adjusted means squares). Tables [6][7][8] show the ANOVA regression analysis results of the components for the Sv, Sz, and Sa parameters (where: DF-degrees of freedom, Seq SS-sums of squares, Adj SS-adjusted sums of squares, and Adj MS-adjusted means squares).…”
Section: Resultsmentioning
confidence: 99%
“…Metal materials obtained with the additive technology feature porosity and areas of varied material cohesion. AlSi10Mg has a good strength, corrosion resistance, low density, and high thermal conductivity compared with other alloys and is of tenfound in aerospace and automotive interior AM components, and in functional prototypes [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…V.Kryzhaniskyy and V.Bushlys [3] studied the cutting tool temperature that develops during rough turning of hardened cold-work tool steel is modeled on the basics of experimental data. Wojciech Zebala and Robert Kowalczyk [4] research the cutting forces (Ff, Fp, Fc) when machining of sintered carbides WC-Co (25% Co) with tools made of polycrystalline diamond PCD. Jinming Zho and Volodymyr Bushlya [5] analysis of subsurface microstructural alterations and residual stresses caused by machining significantly affect component lifetime and performance by influencing fatigue, creep, and stress corrosion cracking resistance.…”
Section: Sujan Debnath Moola Mohan Reddy and Qua Sokmentioning
confidence: 99%
“…Zębala et al [3] published a paper about sintered carbide external turning using a PCD tool with different nose radius and cutting speed, having as output parameter of the cutting force. They found that the nose radius which implied in lower cutting force was 0.2 mm.…”
Section: Introductionmentioning
confidence: 99%